The Revival of Nokia: The Power of Past Recognition of Brand and the Innovativeness - Deviyola Kurnia Ramadhani; Ignatius Hari Santoso (JURNAL STIE SEMARANG, 2023)
The purpose of this research is to find out The Revival Of Nokia: The Power Of Past Recognition Of Brand And The Innovativeness. The population in this study are consumers who currently have purchased a Nokia brand smartphone. The sample in this study are consumers who currently have purchased a Nokia brand smartphone as many as 97 respondents. The sampling technique in this study was using snowball sampling as the sampling technique. The analysis tool used is Smart PLS. The results of the study show that brand recognition has a positive effect on repurchase intention